The cost of Sharia investing : comparative empirical study in Indonesian stock market / Muhammad Rifqi - Rifqi, Muhammad (Faculty of Business and Management, Universiti Teknologi MARA Selangor, 2016)
This study attempts to investigate the financial performance of Jakarta Islamic Index (JII) in comparison with more widely known Jakarta Composite Index (JCI). Using historical data from January 2004 to May 2015, we comprehensively measure returns and risk properties of the indices using mean returns, standard deviation, Sharpe ratio, Treynor ratio, Jensen Alpha, and Value-at-Risk, and evaluate their results. We also perform portfolio simulation to assess the diversification capability of JII from strategic asset allocation perspective. Our findings indicate that despite JII outperforms JCI during pre-crisis in terms of raw and risk-adjusted returns, it underperforms JCI in all other sub-periods. Meanwhile, in terms of risk characteristics, we find that JII is a clear inferior to JCI. Thus, in overall we argue that there is a substantial cost associated with Sharia investing in Indonesian Stock Market. Nevertheless, simulation results indicate that JII could serve as a valuable portfolio diversification tool, in which it succeeds in lowering the risk of the whole portfolio.